Moçambique. Aspectos da Cultura Material - Eduardo Medeiros (Outros Títulos, 2019)
The exhibition "Mozambique: Aspects of Material Culture", as referred to in this catalog, is part of the activities of the 5th Week of African Culture, which over the last four years has been carrying out scientific-cultural actions, including which several ethnographic exhibitions. Through the exposed copies, witnessing of the material culture of a people, have if- you a vision, even partial, of their values transmitted over several generations. Common and utilitarian objects such as benches, chairs, pots, pans, pipes, combs, etc., are adorned with attractive decorative motifs, giving them originality, beauty and a sense of spiritual comfort, indispensable to the well-being of the user in the environment your daily life. A very old and common culture is basketry and matting, which plays an extremely utilitarian role, targeting multiple sectors: agriculture, fishing, trade, storage and drying of products and for domestic use. A wide variety of raw materials are available: palm leaf strips, baobab bark, pineapple or sisal leaf fibers, grass varieties and other plant products. The interweaving of these results in materials design skilled and ingenious demonstrated by the different techniques and models. Basketwork techniques vary between the technique of interlocking, interlacing and the spiral technique, but there are other auxiliaries of various kinds. Geometric and colorful designs give this art of weaving an imprint of remarkable beauty. (Baskets Macondes: n.rs 10, 11 and 12). [...] [MARIA DO ROSÁRIO RODRIGUES MARTINS]